The representation of the female figure in art and the formation of new narratives - Kumm, Rosely (Revista do Colóquio, 2024)
This study analyzes the representation of the female figure in art, especially in classical European art, and its reflections in the media and visual culture that establish the parameters of what is considered beautiful and, by contrast, what is relegated to the realm of the ugly or the grotesque. This discussion paves the way for an analysis of the feminine, in particular, and how it has been shaped and stigmatized by these cultural lenses of beauty and symbolism, revealing the importance of art as a field of knowledge for the construction of affirmative identities and the promotion of new narratives.